Non universality of leptons as a source of new physics from non standard interactions of pseudoscalar mesons - Wasi Uz Zaman; Shakeel Mahmood; Maimoona Razzaq; Abrar Ahmad; Kamran Hussain Tahir (Kuwait Journal of Science)
The rare decays, K+→π+νν¯, B+→π+νν¯ and D+→π+νν¯, are investigated in the frame work of nonstandard neutrino interactions (NSI). It is claimed that NSI are arising due to non-universality of the leptons and bounds on NSI parameters ϵll′uL are determined. For this purpose, the branching ratios (Br) of these processes within the Standard Model (SM) and beyond the SM are calculated by applying the non-universality of the leptons. The NSI in K+→π+νν¯ and B+→π+νν¯ proceed with u quark in the loop while other two with d quark in the loop. Very stringent 1 σ level constrains on non-standard parameters ( ϵττuL and ϵτl′uL ) are pointed out.